THE INFLUENCE OF KV VARIATIONS TO UNIFORMITY CT NUMBER IN SOMATOM EMOTION CT SCAN UNIT USED IN DEPARTMENT OF RADIOLOGY Dr. KARIADI HOSPITAL SEMARANG - , Asih Puji Utami, Lutfi Rusyadi, Subekti Nugraheni (Jurnal Ilmu dan Teknologi Kesehatan, 2010)
This research is conducted in Department of Radiology Dr. Kariadi Hospital Semarang.Â  The purpose is to know the influence of kV variation to uniformity CT number using Somatom Emotion CT Scan Unit. The type of this research is experimental research using analytic study.Â  The experiment is conducted by scanning water phantom 3 (three) times by using kV variations (80 kV, 110 kV, 130 kV). Three slices were made for every kV.Â  CT Number Rate is measured using ROI software.Â  ROI Width used is about 2-3 cm2 (Â± 200-300 pixels). The ROI located in the center scanning area and the surrounded area (clockwise) at 12, 3, 6 and 9. This research is conducted everyday for five days. The urgensi of this study is to ascertain uniformity CT number be in good condition, if its unstandart will difficult to differentiate attenuation coefficient to diagnosis a normaly or pathologis tissue. The result of measurement about CT number shown that the kV election at 80 kV, 110 kV and 130 kV the value of uniformity CT number is belowÂ  0Â±5 HU. The result of research is still in tolerance given by the manual operating book of Somatom Emotion CT Scan Unit.Â  The book stated that the value of HU water is about 0 to Â±4.Â  it means that HU value started from - 4 up to 4.Â  It indicates that Somatom Emotion CT Scan Unit used in Department of Radiology Dr. Kariadi Hospital Semarang has good component in uniformity CT number according to standard. Interpretation result of hypothesis test based on correlation coefficient (r) is equal to 0,473. It is still in the range of 0,25 â¤ r < 0,5 which means the correlation is low. The value â 0,473 (negative) means that the correlation is contradictive. Where the increase of kV value will lead to decrease of noise (CT number fluctuation). It is also mean that uniformity CT number near to 0 (zero), which means the CT number is more uniform. The value of coefficient Determinance ( rÂ²) is 0,224 ( 22,4 %) which means the influence between the increase of kV value to uniformity CT number is equel to 22,4%, the rest Of 77,6% is influenced by the other factors. Keywords: Variation of kV, Uniformity CT number, Quality.